Biodegradation oC n-eicosane and VOCs: Cometabolism in a marine consortium - Flores Valle, Sergio Odín; Ríos Berny, Omar; Fregoso Aguilar, Tomas Alejandro; Herrera Bucio, Rafael; Zapata Peñasco, Icoquih; Mendoza Pérez, Jorge Alberto (2013)
Several batch scale assays were performed in order to establish a correlation between the microbial removals of n-eieosane, in presence of different concentrations of volatile organic compounds (VOCs) which showed a partial removing. The selected VOCs were toluene aod benzene. Results with benzene showed That The removal of This aromatic compounds was decreased in presence of n-eicosane and the lowest removal was obtained when voc concentration was higher. The removal of hydrocarbon was increased when voc concentration was increased. In the essays with toluene, n-eicosane reached a higher removal when voc concentration was increased, but the aromatic compound showed a decrease in its elimination dynamics. Control assays performed with VOCs at 28 mg/L wilhout hydrocarbon showed higher removal dynamics for benzene than toluene. Also control assays of n-eicosane at two different concentrations but without any VOC showed that its removal dynamic decreased in the absence of the aromatic compounds for both assays. The kinetic adjustment obtained for toluene (Hi11 kinetic model) showed that the removal rate of this compound increased while its concentration at water-phase was higher. Although, when it was used a conceotration of 50 mg/L or higher, the removal rate became almost constant. For benzene, the higher removal rate was reached with 38 mg/L. With higher concentration. The kinetic model showed inhibition, so the adjustment analyses fitted for a Monod kinetic model. n-Eicosaoe showed a better adjustment with the Haldane kinetic model with an initial concentration of 188 mg/L for the highest removal rate.